The high-molecular-weight glutenin subunit compositions of wheat varieties bred in Finland - Sontag, Tuula; Salovaara, Hannu; Payne, Peter I (Agricultural and Food Science, 1986)
The composition of high-molecular-weight (HMW) glutenin subunits in 35 Finnish bread wheat cultivars was determined by SDS-polyacrylamide gel electrophoresis. One third of the varieties have one of two HMW glutenin subunit compositions and there are only 17 different compositions in all. Three cultivars, Antti, Kiuru and Panu, are genetically mixed for some of these subunits. Cultivar Tammi (II) contains a novel HMW subunit of glutenin, not detected in any bread wheat previously analysed, and is presumed to be coded by genes on chromosome 1A at the Glu-A1 locus. On the basis of previous work, which related individual subunits to bread-making quality, HMW glutenin subunit quality (Glu-1 quality) scores were calculated for the varieties. The results are related to the bread-making quality of Finnish wheats.